Analisis Aktor Pelaksana Dalam Implementasi Program Bantuan Sosial Beras Sejahtera Di Kelurahan Kasongan Baru Kecamatan Katingan Hilir Kabupaten Katingan - Muhammad Riban Satia; Risdayanti Noor Safitri (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2018)
The purpose of this research is to know how actors role in the implementation of the Rice prosperous assistance Program in the new Kasongan sub-district of Katingan Hilir Katingan regency. The research method used is a qualitative descriptive that is to explain, describe, and represent a phenomenon that exists to solve a problem. In this study there are two data sources, namely the primary data source obtained from interviews with several respondents in the new village of Kasongan, and secondary data sources are obtained from various documents and so on. Based on the results of the study can be concluded that the role of actors in implementing the implementation of the social rice assistance Program in Kasongan New village is still not going well if viewed from the communication and target of the recipient family Benefits. From the problem that the researcher suggested that the village employees more often communicate with the community in Kasongan New village, especially the beneficiaries family of social and social assistance Emphasize again to each Kelurahan or village in order to record the community that is included in the criteria of beneficiaries social rice assistance so that the data can be renewed and the achievement of the purpose of the social assistance of the prosperous rice in Katingan.